Utworzenie Ambasady Rzeczypospolitej Polskiej w ZSRR w 1941 roku - Bujanowska, Beata (Acta Universitatis Lodziensis. Folia Historica, 2002)
The outbreak of the German-Soviet War on 22 Juni 1941 created new political conditions in Europe in wich the settlement of the relationship between the Republic of Poland and Union of Soviet Socialist Republics was almost the necessity for the Polish authorities. The root causes for the agreement with its recent agressor and enemy were, according to General Sikorski’s Government, the possibility of taking care of the Polish population on the USSR territory as well as necessity of enlargement of the Polish Army based on recruits from the East. After long and difficult negotiations representatives of the two states agreed the conditions of the political compromise (under the influence of the British diplomatic service) and on 30 July 1941 the Polish-Soviet agreement was achieved, wich was called after the surnames of signatories as the Sikorski-Maiski Pact where both sides decided to restore diplomatic relations and were obliged to exchange embassadors. In the result of this agreement the polish embassy was reactivated in Moscow in the middle of August 1941. Prof. Stanislaw Kot was the first supervisor of the embassy.